NGHIÊN CỨU THỰC NGHIỆM SỬ DỤNG CHẤT GIA CỐ TRÊN CƠ SỞ VẬT LIỆU POLYME ĐỂ CHỐNG XÓI MÒN CHO Ụ ĐẤT CÔNG TRÌNH QUÂN SỰ - Nguyễn, Phi Long; Hà, Hữu Sơn; Trần, Thị Thu Hằng; Nguyễn, Hồng Thanh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SUMMARY USING SOIL HARDENING ADDITIVES BASED POLYMER MATERIAL TO PREVENT SOIL EROSION FOR MILITARY WORKS This article presents some results about the influence of TS and cement additives on the mechanical properties of hill soil (group A-2-7). It is shown that, the hill soil might be used for building of military mounds when the content of TS additive and cement equals 0.5% and 5% respectively. Some tests were conducted in order to assess the erosion resistance of hill soil added TS additive and cement in the ratio mentioned above. The results showed that, the mixture of TS and cement additives is highly effective in preventing soil erosion. The amount of eroded soil from mound with additives has decreased by 96% when compared with no additives. In particular, the grass can grow normally on the mound surface with these additives.